Development of a disease specific quality of life questionnaire for patients with Graves' ophthalmopathy: the GO-QOL. Issue 7 (1st July 1998) - Terwee, Caroline B; Gerding, Martin N; Dekker, Friedo W; Prummel, Mark F; Wiersinga, Wilmar M
Abstract : AIM: To develop a reliable and valid disease specific quality of life questionnaire (the GO-QOL) for patients with Graves' ophthalmopathy (GO), that can be used to describe the health related quality of life and changes in health related quality of life over time as a consequence of disease and treatment. METHODS: 70 consecutive GO patients (age >18 years) who were referred for the first time to the combined outpatient clinic of the orbital centre and the department of endocrinology completed the 16 questions of the GO-QOL. Additional information on general quality of life and disease characteristics was obtained. Construct validity and internal consistency of the disease specific questionnaire was determined, based on principal component analysis, Cronbach alphas and correlations with MOS-24, three subscales of the SIP, demographic, and clinical measures. RESULTS: The a priori expected subdivision of the questionnaire in two subscales, one measuring the consequences of double vision and decreased visual acuity on visual functioning, and one measuring the psychosocial consequences of a changed appearance, was confirmed in the principal component analysis. Both scales had a good reliability and high face validity. Correlations with other measures supported construct validity. Mean scores (range 0–100) were 54.7 (SD 22.8) for visual functioning and 60.1 (24.8) for appearance (higher score = better health). CONCLUSION: The GO-QOL is a promising tool to measure disease specific aspects of quality of life in patients with GO and provides additional information to traditional physiological or biological measures of health status.